Research on the impact of college students’ “Buddha-like” characteristics on social responsibility and the mediating role of social support - Qi, Zhengnan; Han, Fang (Frontiers in Psychology, 2025)
IntroductionAgainst the backdrop of China’s social transformation, the “Buddha-like” mindset has permeated the college student population, emerging as a subcultural phenomenon that serves as both a stress buffer and a potential developmental risk.MethodsGrounded in social cognitive theory, this study administered a questionnaire survey to 1,147 undergraduate and vocational college students. Utilizing structural equation modeling (SEM), hierarchical regression, and Bootstrap mediation tests, it systematically investigated the pathways through which “Buddha-like” Characteristics influence social responsibility and examined the mediating role of social support.ResultsThe findings revealed that: (1) “Buddha-like” Characteristics can be aggregated into a four-dimensional structure comprising Low Goal Commitment, Low Self-Transcendence, Low Interpersonal Communication, and High Dependence, which overall demonstrated a significant negative association with Social Responsibility; (2) Social Support played a partial mediating role between them, with the indirect path through Family Support being the most prominent; (3) The influence of “Buddha-like” Characteristics exhibited dimensional heterogeneity: Low Goal Commitment had both direct and indirect effect paths; Low Self-Transcendence exhibited a significant suppression effect, where Social Support masked its underlying negative nature; Low Interpersonal Communication exerted its influence entirely indirectly through Social Support; (4) High Dependence displayed characteristics of “Inconsistent Mediation,” reflecting its dual functionality in family versus broader social contexts. Furthermore, the study found that “Buddha-like” Characteristics were more pronounced among undergraduates, students majoring in humanities, sciences, and agriculture, as well as those without Student Positions or Honor Statuses.DiscussionThis research constructs an integrated model, provides new insights into the complex effects of the “Buddha-like” mindset, and identifies the practical pathway of mitigating its negative effects by strengthening social support, particularly Family Support.